Low-temperature sintered high-permeability fine-grain nickel-copper-zinc ferrite material and preparation method thereof

By adjusting the main formula and adding auxiliary components and optimizing the sintering process, the problem of preparing high-permeability fine grain nickel copper-zinc ferrite materials under low temperature conditions is solved, and the permeability stability of the material is achieved in a wide temperature range, meeting the normal use requirements of electronic components in high temperature environments.

CN119899028APending Publication Date: 2025-04-29ZHEJIANG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510082542.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The prior art is difficult to prepare fine grain nickel copper zinc ferrite materials with high permeability under low temperature conditions, and the material has poor permeability stability within a wide temperature range, making it difficult to meet the normal use requirements of electronic components in high temperature environments.

Method used

Low-temperature sintering is promoted by adjusting the Fe2O3, ZnO, NiO and CuO content in the main formula and adding low-melting copper oxide to replace partial nickel oxide. In addition, Bi2O3 and MnO are added as auxiliary components to optimize the sintering process and material formulation to achieve high magnetic permeability and wide temperature stability.

Benefits of technology

It has achieved the preparation of nickel copper-zinc ferrite materials with small grain size and high magnetic permeability under low temperature sintering conditions, and the magnetic permeability changes of the materials within a wide temperature range are relatively stable. It is suitable for scenarios with large temperature changes and meets the normal use requirements of electronic components in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899028A_ABST
    Figure CN119899028A_ABST
Patent Text Reader

Abstract

The invention discloses a low-temperature sintered high-permeability fine-grain nickel-copper-zinc ferrite material and a preparation method thereof. The nickel-copper-zinc ferrite material is prepared from main components and auxiliary components, the main components comprise ferric oxide, zinc oxide, nickel oxide and copper oxide in molar percentage; the auxiliary components comprise the following raw materials: Bi2O3 and MnO. The preparation method of the material comprises the following steps: burdening, mixing, pre-sintering, secondary ball milling, granulating, forming and sintering. The nickel-copper-zinc ferrite prepared by the method has the characteristics of forming smaller crystal grains and sintering under a low-temperature condition, uniform and fine crystal grains of about 2-3 microns are formed under the sintering condition of 920 DEG C, the change of magnetic conductivity along with temperature is relatively stable under the conditions of 100kHz, 500mV and a wide temperature range of 25-120 DEG C, and the magnetic conductivity at 25 DEG C is about 900. In addition, the Curie temperature of the material is kept at about 140 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a soft magnetic ferrite material and a preparation method thereof, in particular to a low-temperature sintered high-permeability fine-grain nickel-copper-zinc ferrite material and a preparation method thereof. Background Art

[0002] As a soft magnetic material, NiCuZn ferrite is widely used in various fields due to its excellent properties such as high resistivity and saturation magnetic induction intensity and good high-frequency performance. With the rapid development of electronic components towards miniaturization and multifunctionality, higher requirements are also placed on the power consumption and other performance of NiCuZn soft magnetic ferrite. Low-temperature co-fired ceramic (LTCC) technology can well meet the needs of device miniaturization and integration. In order to better match LTCC technology, NiCuZn ferrite must be sintered at low temperature. Today, low-power and low-temperature sintered NiCuZn ferrite materials have become the key to the development of LTCC devices.

[0003] In recent years, with the development of planar transformers produced using LTCC technology, the miniaturization of power devices has also been greatly improved. The planar transformers of LTCC process have compact structure, high temperature resistance, and higher strength. They can be well applied to power devices, and thus are widely used in fields such as computers and communications. It is the development trend of planar transformers in the future. Therefore, in summary, the study of NiCuZn ferrite materials with high magnetic permeability and low power consumption under low temperature sintering conditions has far-reaching significance for the rapid development of many electronic products such as LTCC transformers. With the further miniaturization and integration of devices, it is required to prepare sintered NiCuZn ferrite materials with a thickness of ten to tens of microns. This requires that the grain size of nickel-copper-zinc ferrite prepared by low temperature sintering be kept at least below a few microns. At the same time, in order to ensure the performance of the device such as inductance, the prepared nickel-copper-zinc ferrite sintered body is required to maintain a high magnetic permeability. Summary of the invention

[0004] The purpose of the present invention is to provide a low-temperature sintered high-permeability fine-grain nickel-copper-zinc ferrite material and a preparation method thereof in view of the deficiencies in the prior art.

[0005] This patent application discloses a low-temperature sintered high-permeability fine-grain nickel-copper-zinc ferrite material and its preparation method. The material has a μ i The Curie temperature is about 900 and is greater than 140°C. The ZnO content of the main formula of this material is studied. According to the single ion model of magnetocrystalline anisotropy, the magnetocrystalline anisotropy of ferrite is the sum of the anisotropies of various single magnetic ions. 2+After the ions replace the magnetic ions, the number of magnetic ions that produce magnetocrystalline anisotropy is reduced, so the magnetocrystalline anisotropy constant K1 decreases and the magnetic permeability increases. Adding low-melting-point copper oxide to the basic formula of nickel-zinc ferrite to replace part of the nickel oxide promotes the low-temperature sintering of ferrite materials, reducing production costs while ensuring magnetic properties.

[0006] This patent application discloses a low-temperature sintered high-permeability fine-grain nickel-copper-zinc ferrite material and its preparation method. The grain size of the material is 2-3μm, and the initial magnetic permeability μ at 25°C i >900, 1MHz, 20mT, Pcv≤110kW / m at 25℃ 3 .

[0007] This patent application discloses a low-temperature sintered high-permeability fine-grained nickel-copper-zinc ferrite material, its preparation method and finished product. In addition to the innovation of the main formula, Bi2O3 is added as an additive to the material. Adding an appropriate amount of Bi2O3 to the material can accelerate the ion diffusion rate at a lower sintering temperature and promote grain growth. The material modification is first achieved by changing the morphology of magnetic grains and introducing new grain boundary phases through the fluxing effect of Bi2O3 at the microstructural level. When a small amount of Bi2O3 is added, the increase in grain size and the reduction in pores are both beneficial to the movement of domain walls during magnetization, which increases the magnetic permeability of the material. When the Bi2O3 content is further increased, abnormal growth occurs, and the non-magnetic grain boundaries also thicken, which is not conducive to the movement of domain walls during magnetization, and the magnetic permeability decreases. Therefore, the material research selected a suitable content of the additive Bi2O3.

[0008] This patent application discloses a low-temperature sintered high magnetic permeability fine-grained nickel-copper-zinc ferrite material and its preparation method. Under the conditions of optimizing the material formula, combining special doping process and sintering curve, the room-temperature magnetic permeability μ i The grain size is 2-3μm, and the working temperature range is 0±2℃~100±2℃. At the same time, MnO is added as an additive to the material. At a certain concentration, Mn 2+ The ions reduce the magnetostrictive effect, thereby increasing the initial magnetic permeability.

[0009] This patent application discloses a low-temperature sintered high-permeability fine-grained nickel-copper-zinc ferrite magnetic material and its preparation method. The material is sintered at a lower sintering temperature through innovations in the main formula and additives, while improving the material's magnetic permeability and Curie temperature. The material further improves the material's magnetic permeability and improves its overall performance by adjusting the sintering temperature. i >900, Curie temperature T C>140°C. However, if the sintering temperature is too low, the sample will not be sintered completely and fewer grains will be formed, but if it is too high, the grain size of the sample will increase and the idea of ​​fine grains cannot be achieved.

[0010] In summary, the development of a nickel-copper-zinc ferrite material with small grain size and high magnetic permeability obtained under low temperature sintering conditions has important application value.

[0011] The technical solution adopted by the present invention is specifically as follows:

[0012] A method for preparing a low-temperature sintered high-permeability fine-grain nickel-copper-zinc ferrite material, using a low-temperature sintering solid phase reaction method, specifically comprising:

[0013] Step 1, preparing the main component raw materials of nickel-copper-zinc ferrite material for mixed ball milling, wherein the main component raw materials include 49.80% of ferric oxide, 29.40%-29.90% of zinc oxide, 9.90%-10.40% of nickel oxide, and 10.30% of copper oxide in molar percentage;

[0014] Step 2: pre-burning the ball-milled material;

[0015] Step 3, adding auxiliary component raw materials weighed in proportion to the pre-sintered material and performing secondary ball milling; the auxiliary component raw materials include Bi2O3 and MnO;

[0016] Step 4: Granulate and shape the ball-milled material;

[0017] Step 5: sinter the formed material at a temperature of 850°C-950°C, keep it at the sintering temperature for 3-6 hours, and then cool it to below 120°C before taking it out of the furnace. The air atmosphere is also maintained during the cooling process to obtain a high magnetic permeability fine-grained nickel-copper-zinc ferrite material.

[0018] The initial magnetic permeability μ of the prepared material at 25°C i >900, Curie temperature T c >140℃.

[0019] A low-temperature sintered high-permeability fine-grain nickel-copper-zinc ferrite material, the nickel-copper-zinc ferrite material is composed of a main component and an auxiliary component;

[0020] The main components, in terms of molar percentage, include 49.80% of ferric oxide, 29.40%-29.90% of zinc oxide, 9.90%-10.40% of nickel oxide, and 10.30% of copper oxide;

[0021] The auxiliary components include at least one of the following raw materials: Bi2O3, MnO.

[0022] Preferably, the auxiliary component is composed of the following raw materials based on the total weight of the main component: Bi2O3 3000ppm, MnO 2000-4000ppm.

[0023] Preferably, the main components include 49.80% of ferric oxide, 29.40%-29.90% of zinc oxide, 9.90%-10.40% of nickel oxide, and 10.30% of copper oxide; the auxiliary components include 3000ppm of Bi2O3 and 3000ppm of MnO.

[0024] As a preferred embodiment, the main components include 49.80% of ferric oxide, 29.90% of zinc oxide, 9.90% of nickel oxide, and 10.30% of copper oxide; the auxiliary components include 3000ppm Bi2O3, 3000ppm MnO,

[0025] ppm.

[0026] Preferably, the specific process of step one is: mixing the main component with deionized water according to the formula amount, fully ball-milling for 16-24 hours and drying the obtained slurry, and sieving to obtain powder; the amount of deionized water used is 45-55% of the total weight of the main component, preferably 50%.

[0027] Preferably, the specific process of step 2 is: pre-burning the powder obtained in step 1 at a temperature of 750° C.-850° C., and naturally cooling to obtain the pre-burned material.

[0028] Preferably, the specific process of step three is: according to the formula, add auxiliary ingredients and deionized water to the pre-burnt material in step two, perform secondary ball milling for 16-24 hours, and dry to obtain a powder with a particle size of 0.1-1.5 μm; the amount of deionized water used is 45-55% of the total weight of the main ingredients, preferably 50%.

[0029] Preferably, the specific process of step 4 is: adding a polyvinyl alcohol aqueous solution with a mass concentration of 6%-12% to the ball-milled powder obtained in step 3, mixing evenly and granulating to obtain granular material; the weight ratio of the polyvinyl alcohol aqueous solution to the ball-milled powder is 8-15:1, preferably 10:1.

[0030] Preferably, in step 4, the granular material obtained by granulation can be pressed into a magnetic ring; the size of the magnetic ring is Ф20mm*Ф10mm*5mm.

[0031] Compared with the prior art, the high magnetic permeability nickel-copper-zinc ferrite material proposed by the present invention has the following beneficial effects:

[0032] 1. Through a large number of systematic doping test studies, we obtained a high-permeability nickel-copper-zinc ferrite material with fine grains sintered under low temperature conditions, a magnetic permeability greater than 900 at 25°C, and a relatively stable change in magnetic permeability with temperature. This material is suitable for scenes with large temperature changes and ensures the normal use of electronic devices.

[0033] 2. In the main formula of the present invention, by adjusting the content of Fe2O3, NiO and ZnO, the material can have a smaller grain size, ensuring normal use in a high temperature environment. In the auxiliary components of the present invention, the doping amount of the additive Bi2O3 changes the content of the liquid phase during sintering, optimizing the ferrite grains to grow finely and evenly, and the doping of the additive MnO can improve the magnetic permeability of the sample and densify the sample. Combining these two additives, the magnetic permeability temperature stability is good, so that it still has the characteristics of high magnetic permeability not only at high temperatures, but also at a wider temperature.

[0034] 3. The sintering process of the present invention is conducive to the miniaturization and lightweight of electronic components. The sintering temperature is low, which is of great significance to energy saving and environmental protection. The working temperature of the nickel-copper-zinc ferrite material of the present invention can be as low as 25°C and as high as 140°C. It has an ultra-wide working temperature range, and the magnetic permeability changes more stably between 25°C and 120°C.

[0035] The invention protects a wide-temperature high-permeability nickel-copper-zinc ferrite material with a fine grain size sintered under low temperature conditions and a magnetic permeability that changes stably with temperature in a wide temperature range and a preparation method thereof. The prepared nickel-copper-zinc ferrite has a grain size of 2-3 μm, and under the conditions of 100 kHz and 500 mV, within a wide temperature range of 25° C. to 120° C., the magnetic permeability is above 900, and the change of the magnetic permeability within the wide temperature range is relatively stable, being 900±15%, and the magnetic permeability temperature curve at 25° C. to 120° C. is flat, so that the sample has a wider and more stable operating temperature range, thereby meeting the requirements that the magnetic permeability of electronic components is stable within a wide temperature range and better matches the LTCC technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a typical curve diagram of the magnetic permeability temperature characteristic of the nickel-copper-zinc ferrite obtained in an embodiment of the present invention. DETAILED DESCRIPTION

[0037] The present invention mainly focuses on how to make NiCuZn ferrite have the highest possible magnetic permeability and the lowest possible power consumption while sintering at low temperature. Aiming at the influence of raw materials, main formula, additives and preparation process on the microstructure and electromagnetic properties such as magnetic loss of NiCuZn ferrite materials, the main formula for preparing low-temperature sintered NiCuZn ferrite materials, the influence of several different additives on the electromagnetic properties of ferrites and the sintering process used to obtain the best performance are tried and understood, and finally a low-temperature sintered high magnetic permeability fine-grained nickel-copper-zinc ferrite material and its preparation method are obtained.

[0038] The present invention will be further described in detail below in conjunction with the embodiments.

[0039] Example 1

[0040] Step 1, batching and mixing: weigh the main components (Fe2O3, ZnO, NiO, CuO) according to the formula in Table 1, then add deionized water (50% of the total weight of the main components) into a ball mill, mix and ball mill to an average particle size of 0.8-1.2 μm to obtain a slurry, dry it, and sieve it to obtain a powder;

[0041] Step 2: Pre-burning: Pre-burn the obtained powder at a temperature of 800°C for a period of

[0042] 2h, naturally cool to obtain pre-sintered material;

[0043] Step 3, secondary ball milling: add auxiliary component raw materials weighed in proportion to the above pre-sintered material, the auxiliary component is Bi2O3 3000ppm, MnO 3000ppm based on the total weight of the main component, then add deionized water of 50% of the total weight of the main component into the ball mill, perform secondary ball milling and drying to obtain a powder with an average particle size of about 0.9μm;

[0044] Step 4: Granulation: Add a 10 wt% PVA aqueous solution in a weight ratio of 10:1 to the powder obtained in step 3, mix well and granulate to obtain granules for molding;

[0045] Step 5: Molding: Press the granulated granules into magnetic rings of 20mm*10mm*5mm in diameter;

[0046] Step 6, sintering: Place the magnetic ring formed in the above step 5 in a precision atmosphere controlled sintering furnace and sinter at a temperature of 900°C, and keep it at the sintering temperature for 3 hours, then cool it to below 120°C and take it out of the furnace to obtain ferrite.

[0047] The final composition of the ferrite tested by Rigaku Primus II XRF analyzer is roughly consistent with the designed composition (the main component setting composition and XRF test composition results are shown in Table 1). The inductance of the ferrite in the range of -20℃-160℃ is tested by Keysight E4980A precision LCR meter, and then according to the formula To calculate the magnetic permeability, where L s is the inductance, measured in microhenry (μH), L e is the magnetic circuit length of the magnetic ring, in centimeters (cm), N is the number of turns of the coil, A e is the magnetic circuit area of ​​the magnetic ring, in square centimeters (cm 2 ). s -T graph, find L s The intersection of the line connecting 80% and 20% of the maximum value and the temperature axis is the Curie temperature T c .

[0048] In Example 2 to Example 10, the amounts of the main components (Fe2O3, ZnO, NiO, CuO) in Example 1 are adjusted according to Table 1. Other operations are the same as in Example 1. The results are listed in Table 1.

[0049] Table 1

[0050]

[0051] Note: The schemes with * are comparative examples.

[0052] Among the examples shown in Table 1, 6 and 7 are examples of the present invention, and the others are comparative examples.

[0053] From the data in Table 1, we can see that:

[0054] 1) The main components of Examples 6-7 are all within the scope defined by the present invention. By adjusting the content of ZnO and NiO, the initial magnetic permeability of the material at room temperature is maintained at about 900, and the Curie temperature of the material is above 140°C, which can ensure that the material can be used normally in a high temperature environment.

[0055] 2) The Curie temperature of Comparative Examples 1-3 is high but the magnetic permeability is low. On the contrary, the magnetic permeability of Comparative Examples 4-5 is increased but the Curie temperature is decreased. The ZnO content and NiO content of Comparative Examples 8-10 are beyond the scope of the present invention. Although the magnetic permeability of Comparative Examples 8-9 is high at room temperature, the Curie temperature is low. It is impossible to have high magnetic permeability and high Curie temperature at the same time, and it cannot be used in high temperature scenes. Although the Curie temperature of the material of Comparative Example 10 is higher than that of the embodiment, its magnetic permeability at room temperature is low.

[0056] Embodiment 6-13

[0057] The preparation process of ferrite is the same as that of Example 1. The contents of Fe2O3, ZnO, NiO and CuO in the main component formula are fixed to 49.80mol% of Fe2O3, 29.90mol% of ZnO, 9.90mol% of NiO and 10.30mol% of CuO, and the contents of auxiliary components (Bi2O3 and MnO are shown in Table 2, when the Bi2O3 content is changed (Examples 6-10), MnO is fixed to 3000ppm, and when the MnO content is changed (Examples 11-13), Bi2O3 is fixed to 3000ppm), and the results are shown in Table 2.

[0058] Table 2

[0059]

[0060] Note: The schemes with * are comparative examples.

[0061] In the embodiments shown in Table 2, 13 and 17 are embodiments of the present invention, and 11-12, 14-16 and 18 are comparative embodiments.

[0062] From the data in Table 2, we can see that:

[0063] 1) The contents of Bi2O3 and MnO additives in Examples 13 and 17 are within the range specified in the present invention, the Curie temperature of the material reaches 140°C, and the initial magnetic permeability μ at 25°C is i >900, and the permeability changes little in the range of 25-120℃. The permeability temperature curve at 25-120℃ shows a horizontal trend. Under the condition of ensuring the Curie temperature, the permeability is kept high, and the permeability curve of the material is flat in a wide application temperature range, which solves the problem that most wide-temperature high-permeability ferrite materials have stable permeability only in a certain temperature range, and the permeability in other temperature ranges fluctuates greatly with temperature.

[0064] 2) The content of Bi2O3 and MnO additives in Comparative Examples 11-12, 14-16, and 18 exceeds the specified range of the present invention. Although the Curie temperature of the material is around 140°C and the power consumption of the material does not change much, under the conditions of 10kHz, 10mV, and 25°C, μ i Lower, μ i The fluctuations with temperature are large, which does not meet the performance indicators of wide temperature and high permeability ferrite materials.

[0065] Typical curves of the magnetic permeability temperature characteristics of the nickel-copper-zinc ferrites obtained in Examples 11-18 are shown in Figure 1It can be seen that under the conditions of 100kHz and 500mV, the magnetic permeability of the material changes little with temperature in the wide temperature range of 25℃~140℃. The temperature magnetic permeability curve is stable in the range of 25℃~110℃, and the μ i The power consumption of this material at 1MHz / 20mT test conditions at 25°C is 110kW / m 3 It has low power consumption while maintaining high magnetic permeability.

[0066] The above implementation modes are not limitations of the present invention, and the present invention is not limited to the above examples. Any changes, modifications, additions or substitutions made by technicians in this technical field within the scope of the technical solution of the present invention also belong to the protection scope of the present invention.

Claims

1. A method for preparing a low temperature sintered high magnetic permeability fine grain nickel-copper-zinc ferrite material, characterized in that: include: Step 1: prepare the main raw materials of nickel-copper-zinc ferrite material and mix and ball-mill them. The main component raw materials include, by mole percentage, 49.80% of ferric oxide, 29.40%-29.90% of zinc oxide, 9.90%-10.40% of nickel oxide, and 10.30% of copper oxide; Step 2: pre-burning the ball-milled material; Step 3, adding the auxiliary component raw materials weighed in proportion to the pre-sintered material and performing secondary ball milling; The auxiliary component raw material includes at least one of the following raw materials: Bi2O3, MnO; Step 4: Granulate and shape the ball-milled material; Step 5: sinter the formed material at a temperature of 850°C-950°C, keep it at the sintering temperature for 3-6 hours, and then cool it to below 120°C before taking it out of the furnace. The air atmosphere is also maintained during the cooling process to obtain a high magnetic permeability fine-grained nickel-copper-zinc ferrite material.

2. The method according to claim 1, characterized in that: The auxiliary component is composed of the following raw materials based on the total weight of the main component: Bi2O3 3000ppm, MnO 2000ppm-4000ppm.

3. The method according to claim 1, characterized in that: In the step 1, the main component raw material is mixed with deionized water according to the formula amount, fully ball-milled for 16-24 hours, and the obtained slurry is dried and sieved to obtain powder; the amount of deionized water used is 45-55% based on the total weight of the main component.

4. The method according to claim 1, characterized in that: In the step 2, the pre-burning temperature is 750° C.-950° C., and the pre-burned material is obtained by natural cooling.

5. The method according to claim 1, characterized in that: In the step 3, weighed auxiliary raw materials and deionized water are added to the pre-sintered material for secondary ball milling for 16-24 hours, and dried to obtain a powder with a particle size of 0.1-1.5 μm; the amount of deionized water used is 45-55% of the total weight of the main component.

6. The method according to claim 1, characterized in that: In the step 4, a polyvinyl alcohol aqueous solution with a mass concentration of 6%-12% is added to the ball-milled powder obtained in the step 3, and the mixture is fully mixed and uniformly granulated to obtain a granular material; the weight ratio of the polyvinyl alcohol aqueous solution to the ball-milled powder is 8-15:

1.

7. A low-temperature sintered high magnetic permeability fine-grained nickel-copper-zinc ferrite material prepared by the method for preparing a low-temperature sintered high magnetic permeability fine-grained nickel-copper-zinc ferrite material according to any one of claims 1 to 6, characterized in that: The low temperature sintered high magnetic permeability fine grain nickel copper zinc ferrite material has a grain size of 2-3 μm and a Curie temperature T C >140℃, magnetic permeability μ between 25℃-120℃ i It is 900±15%.